2009
DOI: 10.1007/s00421-009-1200-9
|View full text |Cite
|
Sign up to set email alerts
|

Time course of changes in immuneoendocrine markers following an international rugby game

Abstract: Intense exercise is known to cause temporary impairments in immune function. Few studies, however, have investigated the effects of intense competitive exercise on immunoendocrine variables in elite team sport athletes. The aim of this study was to evaluate the time course of changes in selected immunoendocrine and inflammatory markers following an international rugby union game. Blood samples were taken from players (n = 10) on camp entry, the morning of the game (pre), immediately after (post) and 14 and 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
169
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(192 citation statements)
references
References 45 publications
18
169
4
1
Order By: Relevance
“…The effects of these activities also occur after exercise, during the recovery period 20 . In the present study, post-match cortisol concentrations were increased, corroborating the results found by Ispirlidis et al 6 , Cunniffeet al 23 , and Cormack et al 7 . Those studies also showed a significant increase in cortisol concentrations after a game of rugby, a sport with a movement pattern similar to that of soccer.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of these activities also occur after exercise, during the recovery period 20 . In the present study, post-match cortisol concentrations were increased, corroborating the results found by Ispirlidis et al 6 , Cunniffeet al 23 , and Cormack et al 7 . Those studies also showed a significant increase in cortisol concentrations after a game of rugby, a sport with a movement pattern similar to that of soccer.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, previous research suggests that the muscle damage response to rugby competition is linked to physical collisions (13,38,39,42). Taken together, these results indicate that monitoring upper body fatigue after and during intensified periods of competition is important in rugby league players.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it was observed that skeletal muscle activation of nitric oxide synthesis is dependent on heat shock protein-90 (HSP90) expression (Harris et al 2008). In fact, acute exercise increases inflammation, but chronic adaptation to physical exercise also leads to a positive anti-inflammatory response (Cunniffe et al 2010). Physical training also induces antioxidant protection against radiation.…”
Section: Regular Physical Exercise: Adaptation To Oxidative Stress Anmentioning
confidence: 99%